Kajian In vitro Aktivitas Sel-Sel Trofoblas Blastosis Mencit Aging dan Pengaruhnya terhadap Kegagalan Implantasi - Djuwita, Ita; Helmita, Roza; Winarto, Adi; -, Wahyudin (Jurnal Veteriner; Vol 10 No 1 (2009), 2009)
The objectives of this in vitro study were to investigate the hatching rate, the outgrowth diameter andthe activity of mitochondria Nicotiamide Adenin Dinucleotide Dyhidrogenage (NADH)-CoQ reductase ofblastocysts trophoblast cells from aging mice. Blastocysts of aging (age >12 months) and young productive(age 2 months) mice were collected from the cornua utery at day-4 of pregnancy and were cultured inmDMEM medium supplemented with 10% New Born Calf Serum (NBCS), 10% ITS, and 50 ?g/mlgentamicine, in 5% CO2 incubator at 37°C for 10 days. The blastocysts hatching rate and the trophoblastsmonolayer were examined for their diameter outgrowth and the NADH-CoQ reductase activity. The resultsshowed that the hatching rate, the trophoblast outgrowth diameter and the activity of NADH-CoQ reductaseof blastocysts collected from productive mice were significantly higher than those collected from the agingmice (P<0,05). It can be concluded that the impairment of blastocysts implantation especially, in agingmice were caused by the low activity of the NADH-CoQ reductase that play important role in energyproduction needed for the hatching and trophoblast outgrowth.
Keywords: aging mice, implantation, trophoblast cells, hatching, NADH- CoQ R